Melatonin improves cardiac remodeling and brain–heart sympathetic hyperactivation aggravated by light disruption after myocardial infarction. Issue 4 (7th September 2022) - Jiao, Liying; Wang, Yuhong; Zhang, Song; Wang, Yueyi; Liu, Zhihao; Liu, Zihan; Zhou, Yuyang; Zhou, Huixin; Xu, Xiao; Li, Zeyan; Liu, Zhihao; Yu, Zhongyang; et al.
Abstract: Light in the external environment might affect cardiovascular function. The light disruption seems to be related to changes in cardiovascular physiological functions, and disturbing light may be a risk factor for cardiovascular diseases. Prior studies have found that light disruption after myocardial infarction (MI) exacerbates cardiac remodeling, and the brain‐heart sympathetic nervous system may be one of the key mechanisms. However, how to improve light‐disrupted cardiac remodeling remains unclear. Melatonin is an indoleamine secreted by the pineal gland and controlled by endogenous circadian oscillators within the suprachiasmatic nucleus, which is closely associated with light/dark cycle. This study aimed to explore whether melatonin could improve light‐disrupted cardiac remodeling and modulate the brain‐heart sympathetic nervous system. Our study revealed that light disruption reduced serum melatonin levels, aggravated cardiac sympathetic remodeling, caused overactivation of the brain‐heart sympathetic nervous system, exacerbated cardiac dysfunction, and increased cardiac fibrosis after MI, while melatonin treatment improved light disruption‐exacerbated cardiac remodeling and brain‐heart sympathetic hyperactivation after MI. Furthermore, RNA‐Seq results revealed the significant changes at the cardiac transcription level. In conclusion, melatonin may be a potential therapy for light‐disrupted cardiac remodeling.